STRATEGI ORANG TUA YANG BEKERJA DALAM MENDIDIK ANAK USIA DINi - Thariq Riawan; Muhammad Ronny Zulian; Adduha Karunia (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
This study aims to determine Parents' Strategies in educating and developing Children from Early Age to Adult and the Role of Parents in balancing between Work and Family or Work Life Balance in everyday life. The results of this study indicate that parents have several obstacles and factors in applying the concept of work life balance, but have one strategy, namely authoritative parenting. The combined pattern of Authoritarian Parenting and Pessimistic Parenting. This can be seen from the 2 dimensions given, namely the Dimensions of Control and Warmth, this process must also be carried out consistently and responsibly so that it is carried out properly. Research using qualitative methods with descriptive research type. With secondary data sources through national and international journal articles and using other sources such as online media, social media (youtube, Instagram, Facebook and Twitter). From the results mentioned, it can be concluded that work and personal life as well as the role of parents in educating children are the most important things in order to create a golden generation, where the generation is able to provide a polite attitude, carry out responsibilities towards work and personal life, and most importantly is that children are able to become people who carry out all their activities in a social environment well.